Anísio Teixeira e o sistema nacional de educação : contribuições para o debate sobre as políticas educacionais no Brasil. - Nascimento, Rosenery Pimentel do (2012)
This is a theoretical research which aims, as a starting point, for the analysis of the concept of Sistema Nacional de Educação (National System of Education) in the works of Anísio Teixeira, placing this discussion in the historical and political scene of the Brazilian education. The main concern was to understand which basis and which arguments supported his defense of the national organization of education. It identifies up to which extent the arguments circulated, and still circulate amid the debates and tensions that are stablished in the discussion around the constitution of a National System of Education, highlighting the educator’s contribution in the field of the educational policies. For such purpose, this research uses the documental and bibliographic analysis of 12 works by Anísio Teixeira based on three great axis or category: quality and quantity; public and private; centralization and decentralization. Along this path, the production and action of Anísio Teixeira marked the course of the public policies for education that account for the presence of some of these directions and principles in our current organization. The ideas worked, and still work, in a permanent field of action, which sustains the contemporaneity of the works as an instrument to fight for the consolidation of a national project for education which is still moving in a place of imprecision and disputes. In the final considerations, the ideas highlighted that the works of Anísio Teixeira defined the challenges for the organization of a national education as a political, financial, and professional problem. This way, this perception identifies the current need for the improvement of the Brazilian federative model in order to consolidate a National System of Education.